Recent advances and future of immunotherapy for glioblastoma. (2nd October 2016) - Kamran, Neha; Calinescu, Alexandra; Candolfi, Marianela; Chandran, Mayuri; Mineharu, Yohei; Asad, Antonela S.; Koschmann, Carl; Nunez, Felipe J.; Lowenstein, Pedro R.; Castro, Maria G.
ABSTRACT: Introduction : Outcome for glioma (GBM) remains dismal despite advances in therapeutic interventions including chemotherapy, radiotherapy and surgical resection. The overall survival benefit observed with immunotherapies in cancers such as melanoma and prostate cancer has fuelled research into evaluating immunotherapies for GBM. Areas covered : Preclinical studies have brought a wealth of information for improving the prognosis of GBM and multiple clinical studies are evaluating a wide array of immunotherapies for GBM patients. This review highlights advances in the development of immunotherapeutic approaches. We discuss the strategies and outcomes of active and passive immunotherapies for GBM including vaccination strategies, gene therapy, check point blockade and adoptive T cell therapies. We also focus on immunoediting and tumor neoantigens that can impact the efficacy of immunotherapies. Expert opinion : Encouraging results have been observed with immunotherapeutic strategies; some clinical trials are reaching phase III. Significant progress has been made in unraveling the molecular and genetic heterogeneity of GBM and its implications to disease prognosis. There is now consensus related to the critical need to incorporate tumor heterogeneity into the design of therapeutic approaches. Recent data also indicates that an efficacious treatment strategy will need to be combinatorial and personalized to the tumor genetic signature.